KEANEKARAGAMAN SERANGGA PADA TUMPANGSARI TANAMAN PANGAN SEBAGAI TANAMAN SELA DI PERTANAMAN KELAPA SAWIT BELUM MENGHASILKAN - LUTFI ARIFIN; MOKHAMAD IRFAN; INDAH PERMANASARI; AULIA RANI ANNISAVA; AHMAD TAUFIQ ARMINUDIN (Jurnal Agroteknologi, 2016)
Plant intercropping that interplanted with young palm oil plantation indicated that there was change on ecosystem balance which resulted diversity alteration of insect as bio indicator area. The objective of the research was to obtain information on diversity of insect related to its intercropping system interplanted with young palm oil plantation. The research was conducted from December 2015 to February 2016 at privately-owned oil palm plantation, Kualu district, Kampar regency, Riau province. Descriptive methods by range survey on corn monoculture, soybean monoculture, bera, between corn and soybean intercropping in young palm oil area were used as experimental methods. Insect sampling was conducted by using pitfall trap, sweeping net and hand collection at 16 research units. The result showed that there were ten different insect ordo consisted of 50 families in all intercropping system sampled in this study. Diversity index (H’) reached as high as 3.07 with the best average (E=0.07) that was observed in soybean monoculture. Corn - soybean intercropping posessed the highest point of insect dominance (0.34), which is mean that there was only one kind of insect dominated on the community. The utilization of soybean monoculture system interplanted in young palm oil plantation is best to be used as a reference of ecological indicator on environment utilization, due to the reason that the existence of pest is balanced by the predator.